Design and Research of Automatic Tool Changer System for Multistation Spring Forming Machine. (1st December 2020) - Li, Wei; Wang, Decheng; Cheng, Peng
Abstract : Currently, the spring machine tool is fixed by means of manual clamping and positioning by bolts. The automation of the tool change is low, and the accurate value of the tool position cannot be determined. The automatic tool change system for spring machine was designed by using the standard functional parts of the automatic tool change system of the machining center. It mainly includes the design of the automatic loose clamp device and that of the multispindle automatic tool change arm. After static analysis, the deformation of the automatic tool change arm is 0.153 mm, which satisfies the requirements for usage. Kinematic analysis of the designed automatic tool change arm was carried out. After actual verification, the designed automatic tool change system of spring machine realizes the functions of the tools automatic replacement and positioning of the spring machine, which improves the automation of the spring forming equipment.